2015
DOI: 10.1007/s10973-015-5034-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volume concentration and temperature on viscosity and surface tension of graphene–water nanofluid for heat transfer applications

Abstract: In the present study, the effect of volume concentration (0.05, 0.1 and 0.15 %) and temperature (10-90°C) on viscosity and surface tension of graphene-water nanofluid has been experimentally measured. The sodium dodecyl benzene sulfonate is used as the surfactant for stable suspension of graphene. The results showed that the viscosity of graphene-water nanofluid increases with an increase in the volume concentration of nanoparticles and decreases with an increase in temperature. An average enhancement of 47.12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(54 citation statements)
references
References 45 publications
6
48
0
Order By: Relevance
“…Baby and Sundara [97] presented a technique for preparing the copper oxidedecorated graphene-dispersed nanofluids. Firstly, carboxyl Silicone oil Functionalized GNS MHM, then synthesized 0.0-0.07 mass% [130] EG DI NDG-MNT HM, then CVD 0.005-0.03 vol% 0.005-0.02 vol% [131] DW + SUR GNSs SBM 0.05 mass% [132] Kerosene + SUR GNPs SBM 0.005-0.2 mass% [133] DW GNSs SBM 0.003-0.009 mass% [134] DW + SUR GR SBM 0.05-0.15 mass% [192] EG GO MHM 0.1-5 vol% [193] DW Phenyl-sulfonic-functionalized GR SBM 0.02-1 vol% [194] DI GO MHM 0.005-0.01 mass% [195] EG GO MHM 0.01-0.05 mass% [196] DW GNSs SBM 0.003-0.006 mass% [197] DI GNPs SBM 0.025-0.1 mass% [198] DW GNPs SBM 1 mass% [199] DW + SUR GNPs SBM 0.05-0.15 vol% [200] DW GNSs SBM 0.001-0.01 mass% GR graphene, GI graphite, NP nanoparticle, SUR surfactant Then, the functionalized graphene was utilized to decorate the CuO nanoparticles with the help of CuCl 2 and NaBH 4 and NaOH. Baby and Ramaprabhu [98] and Kole and Dey [105] utilized dried GO to produce hydrogen exfoliated graphene in hydrogen at 200 °C.…”
Section: Preparation Of Nanofluidsmentioning
confidence: 99%
“…Baby and Sundara [97] presented a technique for preparing the copper oxidedecorated graphene-dispersed nanofluids. Firstly, carboxyl Silicone oil Functionalized GNS MHM, then synthesized 0.0-0.07 mass% [130] EG DI NDG-MNT HM, then CVD 0.005-0.03 vol% 0.005-0.02 vol% [131] DW + SUR GNSs SBM 0.05 mass% [132] Kerosene + SUR GNPs SBM 0.005-0.2 mass% [133] DW GNSs SBM 0.003-0.009 mass% [134] DW + SUR GR SBM 0.05-0.15 mass% [192] EG GO MHM 0.1-5 vol% [193] DW Phenyl-sulfonic-functionalized GR SBM 0.02-1 vol% [194] DI GO MHM 0.005-0.01 mass% [195] EG GO MHM 0.01-0.05 mass% [196] DW GNSs SBM 0.003-0.006 mass% [197] DI GNPs SBM 0.025-0.1 mass% [198] DW GNPs SBM 1 mass% [199] DW + SUR GNPs SBM 0.05-0.15 vol% [200] DW GNSs SBM 0.001-0.01 mass% GR graphene, GI graphite, NP nanoparticle, SUR surfactant Then, the functionalized graphene was utilized to decorate the CuO nanoparticles with the help of CuCl 2 and NaBH 4 and NaOH. Baby and Ramaprabhu [98] and Kole and Dey [105] utilized dried GO to produce hydrogen exfoliated graphene in hydrogen at 200 °C.…”
Section: Preparation Of Nanofluidsmentioning
confidence: 99%
“…Surface tension is a crucial parameter in the analysis of heat transfer phenomena such as pool boiling since it affects surface wettability and bubble growth [146]. On the measurement of surface tension of nanofluids, Ahammed et al [147] measured the surface tension of graphene/water nanofluids and showed that with increasing the temperature and nanofluid concentration the surface tension decreases. They developed a correlation as:…”
Section: Surface Tension ( Nf  )mentioning
confidence: 99%
“…It was also confirmed that the empirical model proposed by Adio et al (13) describes the enhancement of the viscosity in MgO-EG nanofluids correctly. It was presented that it is possible to model an increase of the viscosity by using modified K-D model (7) a second degree polynomial (12). It has been shown that the enhancement of thermal conductivity can be modeled also by using a second degree polynomial (20), and the classical models of thermal conductivity do not describe the MgO-EG nanofluids correctly.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in thermal conductivity of nanofluids containing various types of nanoparticles was intensively studied [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. However, when planning the practical use of nanofluids, it should be taken into account that with increasing concentration of the nanoparticles in a liquid its viscosity increases [19,20,26].…”
Section: Introductionmentioning
confidence: 99%